Nirmana Motion Graphic Video: Innovation in Learning Design Principles and Elements - Deny Tri Ardianto; Arif Ranu Wicaksono; Sayid Mataram; RahmanuWidayat (Mudra Jurnal Seni Budaya, 2024)
The use of technology in education has become increasingly important in facilitating effective learning. However, the lack of diversity and innovation in using technology to develop learning materials poses new challenges for educators. In response, this research aims to develop and test the feasibility of a motion graphic video called Nirmana, which includes learning materials on design elements and principles. The research and development (R&D) process applied the ADDIE model to develop the motion graphic video media. The media testing involved 101 design major students. The data collection used questionnaires, observations, interviews, and documentation, which were analyzed using qualitative and quantitative methods. The result of this research is a Nirmana motion graphic video with learning materials about the elements and principles of design. The media was field-tested based on student assessment using the mean results per aspect. The assessment criteria included clarity of information and instructions, media attractiveness, usability and accessibility of media, and material arrangement and use of illustrations. The results showed that the Nirmana motion graphic video media received good to excellent scores on all of these assessment criteria. Specifically, the clarity of information and instructions received a good score of 78.7%, the media attractiveness received an excellent score of 81.7%, the usability and accessibility of media received an excellent score of 89.6%, and the material arrangement and use of illustrations received an excellent score of 85.8%. These results indicate that the developed Nirmana motion graphic video media is suitable for use as a design learning media. Furthermore, this research suggests that using technology to develop relevant and innovative learning materials can positively impact student attitudes and interest in learning design.